Forward Contract Hedging Analysis as a Protection Effort Transaction Exposure: (Case Study at PT. Akasha Wira International, Tbk) - Windayu, Cinde Ririh (International Journal of Business, Law, and Education, 2024)
The purpose of this research is to identify the risks related to currency fluctuations that arise from transactions in foreign currencies or other currencies. A company must be capable of managing foreign exchange activities in order to reduce or eliminate risks. One way to do that is to carry out hedging trades. You may ensure that future fluctuations in foreign exchange rates won't affect the foreign exchange rate utilized for payments (outflow) or the amount of foreign currency received (inflow) by using hedging. Both a qualitative descriptive research design and a case study approach are used in this study. A case study called PT Akasha Wira International, Tbk was used